Motion og sundhed i et programmatisk perspektiv - Skovgaard, Thomas (Forum for Idræt, 2002)
Motion og sundhed som en arena for tilrettelæggelse af offentlig politik og Folkesundhedsprogrammet fra 1999. Exercise and health in a programmatic perspective From a political angle attention is regularly focused on the presumed connection between exercise and health. Generally speaking, there is interest in integrating exercise even more closely than has been the case to date into the health-oriented work which takes place in all parts of society – though most markedly in or with the participation of the public sector. But what progress is in fact being made in the realisation of the various schemes for allowing exercise and health to interact when it comes to actual initiatives on the ground? This is the fundamental question which this article attempts to tackle. At a more concrete level the aim is to analyse health and exercise as an arena for the planning of public policy. The Nyrup Rasmussen government’s Programme for Public Health (FSP) of 1999 has been taken as a starting point. The choice of this programme as a basis is due to the fact that we can in a small way begin to evaluate its impact. Towards the end of September 2002 the government then in power presented a review of the public health programme. To date this mostly consists of words on paper. Since the two national health programmes of 1999 and 2002 respectively resemble each other to a substantial extent – both in respect to content and to the administrative and social circumstances in which they are realised – it is reasonable to presume that what has proved true of the 1999 Public Health Programme will in broad terms also be true of the 2002 Health Programme. This article attempts to answer the following questions: Why and how did we actually get a public health programme? Why did it appear in the year 1999 and are we to regard it in isolation or is there some purpose in placing it in a historical and international perspective? Why is exercise included as an explicit theme in the public health programme? What are the aims of the public health programme in relation to exercise and are they in the process of being realised? The article’s second question is appended to the endless debate regarding whether and under what conditions exercise is healthy. From a precise understanding of what health and exercise are, the article will briefly touch on this question. The article’s third question demands a description of the health programme’s factual content, which leads on to an assessment of whether specific benchmarks are in the process of being attained. In this respect the article focuses exclusively on the subject of exercise. What of the future? An assessment of the public health programme is valuable in itself, but its value increases substantially if this descriptively formulated assessment is used to suggest what possible scenarios the future might hold for public health and for an area such as exercise.